Fostering creativity - Press, Harvard Business School (Boston Harvard Business Review Press, 2010)
Every day on the job, you face common challenges. And you need immediate solutions to those challenges. The Pocket Mentor Series can help. Each book in the series is packed with handy tools, self-tests, and real-life examples to help you identify your strengths and weaknesses and hone critical skills. Whether you're at your desk, in a meeting, or on the road, these portable, concise guides enable you to tackle the daily demands of your work with speed, savvy, and effectiveness. The latest volume in the series: Fostering Creativity To survive in today's hypercompetitive climate, businesses must innovate constantly. Innovation hinges on creativity--generating novel and useful ideas. By fostering creativity in your team, you help unleash your company's innovative powers. But this requires a disciplined process for leveraging employees' unique experiences, thinking styles, and expertise.